Enabling Things to Talk Designing IoT solutions with theIoT Architectural Reference Model - Bassi, Alessandro; Bauer, Martin; Fiedler, Martin; Kramp, Thorsten; van Kranenburg, Rob; Lange, Sebastian; Meissner, Stefan (Springer Nature, 2013)
Information Systems Applications (incl. Internet); Business IT Infrastructure; Computer Appl. in Administrative Data Processing; Operations Management; Software Engineering; Special Purpose and Application-Based Systems; Business Information Systems; Ubiquitous Computing; Reference Architecture; Spatio-Temporal Systems; Smart Objects; Supply Chain Management; IoT; SCM; Web Applications; Internet of Things; Smart Homes; RFID